High-strength rare earth magnesium alloy and preparation process thereof
By adding Sm elements to magnesium alloys and combining hot extrusion and heat treatment processes, the morphology and distribution of LPSO phases are regulated, and the problems of low strength and high cost of magnesium alloys are solved, and the preparation of high-strength magnesium alloys is realized, which is suitable for aerospace and automobile manufacturing fields.
Patent Information
- Application Number
- CN202510595967.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-09
- Publication Date
- 2025-07-25
AI Technical Summary
The existing magnesium alloy has low strength, high added amount of rare earth elements, and limited LPSO phase regulation capabilities, which affect performance stability and repeatability.
The rare earth element samarium (Sm) is added to the Mg-Ni-Gd alloy, and combined with hot extrusion and heat treatment processes, the grains are refined and the morphology and distribution of the LPSO phase are regulated.
It significantly improves the strength of magnesium alloys, reduces the use of rare earth elements, reduces production costs, improves performance stability and repeatability, and is suitable for aerospace and automobile manufacturing fields.
Smart Images

Figure CN120366612A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal materials and relates to a high-strength rare earth magnesium alloy and a preparation process thereof. Background Art
[0002] As the lightest structural material in current engineering applications, magnesium alloys have shown extremely broad application prospects in many fields such as aerospace, automobile manufacturing, and the electronics industry due to their significant advantages such as high specific strength and high specific stiffness. However, the key problem of the low absolute strength of magnesium alloys has greatly limited their further promotion and application in more scenarios. In view of this, the development of magnesium alloy materials with higher strength has become a hot topic and key direction in the field of magnesium alloy research.
[0003] In the process of alloying research on magnesium alloys, the addition of rare earth elements has been proven to be an effective strengthening method. Taking Mg-Ni magnesium alloys as an example, when an appropriate amount of rare earth elements is added to them, it can produce many positive effects. On the one hand, the addition of rare earth elements can effectively refine the alloy grains, reduce the grain size, increase the number of grain boundaries, and thus enhance the mechanical properties of the alloy. On the other hand, rare earth elements can promote the formation of long-period stacking phase (LPSO phase). As a special strengthening phase, LPSO phase plays an important role in magnesium alloys. It can effectively hinder dislocation movement, increase the resistance to dislocation movement, and enable the alloy to withstand greater stress without plastic deformation when subjected to force. At the same time, the formation of LPSO phase can further refine the grains, improve the mechanical properties of magnesium alloys from multiple dimensions, and significantly improve the strength of the alloy.
[0004] Although the strength of magnesium alloys has been improved to a certain extent by adding rare earth elements, this technology still has some problems that need to be solved. First, the amount of rare earth elements added is usually large. Rare earth elements are rare metals with high mining and refining costs. Adding a large amount of rare earth elements will lead to a significant increase in the production cost of the alloy, which is not conducive to the large-scale industrial production and wide application of magnesium alloys. Second, the existing technology has limited control over the LPSO phase. In the actual production process, it is difficult to accurately control the morphology, size and distribution of the LPSO phase, which affects the stability and repeatability of the performance of the magnesium alloy to a certain extent, limiting the further improvement of the performance of the magnesium alloy.
[0005] Therefore, how to improve the ability to precisely control the LPSO phase to achieve better performance improvement of magnesium alloys has become an important challenge facing the current magnesium alloy research field, and is also the key issue that this patent application is committed to solving. Summary of the invention
[0006] In view of this, the purpose of the present invention is to provide a high-strength rare earth magnesium alloy and its preparation process. By adding the rare earth element samarium (Sm) to the Mg-Ni-Gd alloy and combining hot extrusion and heat treatment processes, the grains of the magnesium alloy are refined, and the morphology and distribution of the LPSO phase in the magnesium alloy are regulated, thereby improving the strength of the magnesium alloy.
[0007] To achieve the above object, the present invention provides the following technical solutions:
[0008] A preparation process of a high-strength rare earth magnesium alloy, comprising the following steps:
[0009] (1) Melting: Melting pure magnesium, Mg-25Ni master alloy, Mg-30Gd master alloy, and Mg-30Sm master alloy into an alloy ingot;
[0010] (2) Homogenization treatment: After turning the surface of the alloy ingot smooth, wrapping it with aluminum foil, then burying it in a medium crucible with graphite powder, and placing the crucible in a heat treatment furnace. Heat it to 300°C and hold for 1 hour, then heat it to 530°C and hold for 12 hours. After the holding is completed, cool it with water;
[0011] (3) Hot extrusion: Processing the homogenized alloy ingot into a cylindrical blank, preheating it together with the die, and then loading it into an extruder for forward extrusion. The extrusion parameters are: extrusion temperature 420°C, extrusion speed 1.5 - 2.5 m·min -1 , extrusion ratio 10.24:1, and cool it with water after extrusion;
[0012] (4) Aging treatment: Cutting the hot-extruded bar into cylindrical bars, then wrapping it with aluminum foil, burying it in a medium crucible with graphite powder, and holding it at 200°C for 26 hours. After the holding is completed, cool it with water.
[0013] Further, step (1) includes the following steps:
[0014] a) Alloy raw material preparation: Machining pure magnesium, Mg-25Ni master alloy, Mg-30Gd master alloy, and Mg-30Sm master alloy into blocks and grinding off the oxide film on their surfaces;
[0015] b) Resistance furnace heating: First, heat the resistance furnace to 600°C, and then heat it to 750°C after the temperature stabilizes. At the same time, dry and preheat the crucible;
[0016] c) Adding master alloy: After the crucible is preheated to above 300°C, place pure magnesium in the crucible, place the crucible in the resistance furnace, and introduce the protective atmosphere SF6 + CO2. After the pure magnesium melts, successively add Mg-25Ni, Mg-30Gd, and Mg-30Sm master alloys. After complete melting, adjust the furnace temperature to 730°C and hold for 10 minutes;
[0017] d) Stirring and impurity removal: After power-off, stir for 5 minutes, then heat the resistance furnace back to 720 °C, let it stand for 2 minutes, and then filter out the impurities;
[0018] e) Cooling: Take out the crucible and cool it in cold water to room temperature, then take out the alloy ingot.
[0019] Furthermore, in step (1) a), the purity of the pure magnesium is 99.99 wt.%.
[0020] Furthermore, in step (1) c), the volume ratio of the protective atmosphere SF6 + CO2 is 1:99.
[0021] Furthermore, in step (1) d), use a long-handled ladle to filter out the impurities.
[0022] Furthermore, in step (2), the time taken to heat up to 300 °C is 2 hours, and the time taken to heat up to 530 °C is 2 hours.
[0023] Furthermore, in step (3), the preheating temperature of the mold and the alloy blank is 420 °C, and the preheating time is 2 hours.
[0024] Furthermore, in step (3), the homogenized alloy ingot is processed into a cylindrical blank with a diameter of Φ80 mm; in step (4), the hot-extruded bar is cut into cylindrical bars with a length of 70 mm
[0025] Furthermore, in the alloy composition of the alloy ingot, the atomic percentages of each element are: Ni: 0.75%, Gd: 1.0%, Sm: 0.2 - 0.8%, and the rest is Mg.
[0026] A high-strength rare-earth magnesium alloy is obtained by the described preparation process, and the atomic percentages of each element in its alloy composition are: Ni: 0.75%, Gd: 1.0%, Sm: 0.2 - 0.8%, and the rest is Mg.
[0027] The beneficial effects of the present invention are as follows:
[0028] 1. The present invention proposes a high-strength rare-earth magnesium alloy and its preparation process. By introducing the Sm element into the magnesium alloy and combining hot extrusion and heat treatment processes, the long-period stacking ordered phase (LPSO phase) in the alloy is effectively regulated. The quantity of the LPSO phase in the alloy increases significantly, the size becomes finer, and the distribution becomes more dispersed. This optimization of the microstructure significantly improves the mechanical properties of the magnesium alloy, making its tensile strength reach 385 - 417 MPa, and successfully preparing a high-strength magnesium alloy. This process makes full use of the synergy between the characteristics of the Sm element and advanced processing technologies, providing a new solution for improving the performance of magnesium alloys.
[0029] 2. The Sm element plays multiple important roles in this technical solution. First of all, as a light rare earth element, Sm has an atomic radius similar to that of Gd and a relatively high solubility in magnesium alloys (about 5.8 wt.%), which can effectively replace the Gd element in the LPSO phase and promote the formation of more LPSO phases. After adding the Sm element to the alloy, its strength is significantly improved through three mechanisms: solid solution strengthening, second-phase strengthening, and fine-grain strengthening. Secondly, the cost of the Sm element is much lower than that of the expensive rare earth element Gd. By adding the Sm element, the content of Gd in this invention is reduced to only 1.0 at.%, greatly reducing the demand for high-cost rare earth elements, and thus significantly reducing the preparation cost of magnesium alloys. This strategy of "replacing high with low" not only achieves performance improvement but also takes into account economic benefits, laying a foundation for the large-scale application of magnesium alloys.
[0030] 3. The innovation of this technical solution lies in the precise regulation of the LPSO phase by the Sm element, breaking through the bottleneck between the strength improvement and cost control of traditional magnesium alloys. By regulating the quantity and distribution of the LPSO phase, the strength of the alloy is significantly increased; at the same time, the design of reducing the dosage of the Gd element effectively optimizes the cost structure. The uniqueness of this method is that while improving the mechanical properties of magnesium alloys, it enhances their application potential in fields such as aerospace and automotive manufacturing. The practicality of the process is not only reflected in the dual advantages of performance and cost but also in its strong operability and easy industrial promotion. This technical solution with both innovation and practicality opens up a new path for the development and application of high-strength magnesium alloys and has broad market prospects.
[0031] Other advantages, objectives, and features of the present invention will be described to some extent in the subsequent specification, and to some extent, will be obvious to those skilled in the art based on the study of the following text, or can be taught from the practice of the present invention. The objectives and other advantages of the present invention can be realized and obtained through the following specification. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] In order to make the objectives, technical solutions, and advantages of the present invention clearer, the present invention will be described in detail preferably with reference to the accompanying drawings, where:
[0033] Figure 1 is a flowchart of a preparation process for a high-strength rare earth magnesium alloy;
[0034] Figure 2 is the tensile stress-strain curves of the magnesium alloys in Examples 1 - 4 and Comparative Example 1;
[0035] Figure 3Microstructure diagrams of the magnesium alloys of Examples 1 to 4 and Comparative Example 1, where the grayish-white phase in the figure is the LPSO phase; among them, Figure (a) is Comparative Example 1, Figure (b) is Example 1, Figure (c) is Example 2, Figure (d) is Example 3, and Figure (e) is Example 4;
[0036] Figure 4 For Figure 3 The phase area fraction diagram of the LPSO phase therein; among them, from left to right are Comparative Example 1, Example 1, Example 2, Example 3, and Example 4 in sequence. Detailed implementation manners
[0037] The following uses specific specific examples to illustrate the implementation manners of the present invention. Those skilled in the art can easily understand other advantages and effects of the present invention from the content disclosed in this specification. The present invention can also be implemented or applied through other different specific implementation manners. Various details in this specification can also be modified or changed based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the diagrams provided in the following examples only illustrate the basic concept of the present invention in a schematic manner. Without conflict, the following examples and the features in the examples can be combined with each other.
[0038] Among them, the attached drawings are only used for exemplary illustration, showing only schematic diagrams, rather than physical diagrams, and cannot be understood as a limitation to the present invention; in order to better illustrate the embodiments of the present invention, some components in the attached drawings will be omitted, enlarged, or reduced, which does not represent the size of the actual product; for those skilled in the art, it is understandable that some well-known structures and their descriptions in the attached drawings may be omitted.
[0039] In the attached drawings of the embodiments of the present invention, the same or similar reference numerals correspond to the same or similar components; in the description of the present invention, it should be understood that if there are terms such as "upper", "lower", "left", "right", "front", "rear", etc. indicating the orientation or positional relationship, it is based on the orientation or positional relationship shown in the attached drawings. It is only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation. Therefore, the terms describing the positional relationship in the attached drawings are only used for exemplary illustration and cannot be understood as a limitation to the present invention. For those of ordinary skill in the art, the specific meanings of the above terms can be understood according to specific circumstances.
[0040] Please refer to Figure 1 , which is a preparation process of a high-strength rare-earth magnesium alloy, specifically including the following steps:
[0041] 1) Melting:
[0042] ① Alloy raw material preparation: The raw materials: pure magnesium (99.99 wt.%), Mg-25Ni (wt.%) master alloy, Mg-30Gd (wt.%) master alloy, and Mg-30Sm (wt.%) master alloy are machined into appropriately sized blocks, and the oxide film on their surfaces is polished off with coarse sandpaper. After the alloy is polished to a shiny finish, it is packaged in a sealed bag for standby;
[0043] ② Resistance furnace heating: Set the temperature control program of the resistance furnace. First, heat the resistance furnace to 600 °C. After the temperature inside the furnace stabilizes, heat the resistance furnace to 750 °C. At the same time, dry and preheat the crucible coated with boron nitride release agent;
[0044] ③ Adding master alloy: After the crucible is completely dried and preheated to above 300 °C, place the pure magnesium in the crucible and then place the crucible in the resistance furnace. At the same time, introduce a protective atmosphere of SF6+CO2 (volume ratio approximately 1:99). After the pure magnesium is completely melted, add the three master alloys of Mg-25Ni (wt.%), Mg-30Gd (wt.%), and Mg-30Sm (wt.%) into the stainless-steel crucible in sequence. After they are completely melted, adjust the furnace temperature to 730 °C and hold for 10 min;
[0045] ④ Stirring and impurity removal: After powering off the resistance furnace, use an electric stirrer to stir from bottom to top for 5 min to make the alloy melt as uniform in composition as possible. The resistance furnace is reheated to 720 °C, and after standing for 2 min, use a long-handled ladle to filter out impurities;
[0046] ⑤ Cooling: After stirring and impurity removal, take out the crucible and slowly place it in cold water for water cooling. After cooling to room temperature, take out the alloy ingot;
[0047] 2) Homogenization treatment: After turning the surface of the alloy ingot obtained by melting smooth, wrap it with aluminum foil, and then bury it completely with graphite powder in a stainless-steel crucible. Place the crucible in a heat treatment furnace. Set the temperature to rise from room temperature to 300 °C in 2 h, hold for 1 h, then rise to 530 °C in 2 h, hold for 12 h, and after the holding is completed, take it out for water cooling;
[0048] 3) Hot extrusion: Process the alloy ingot that has completed the homogenization treatment into a cylindrical blank with a diameter of Φ80 mm. Preheat the alloy blank and the die at 420 °C for 2 h. After the preheating is completed, quickly load the die and the alloy blank into the extruder in sequence for forward extrusion. After extrusion is completed, perform cooling, and the cooling method is water cooling. The extrusion parameters are as follows: extrusion temperature: 420 °C, extrusion speed: 1.5 - 2.5 m·min -1 , extrusion ratio: 10.24:1;
[0049] 4) Aging treatment: The bars obtained after hot extrusion are cut into cylindrical bars with a length of 70 mm. The cut bars are wrapped with aluminum foil and buried in graphite, then placed in a crucible and kept at 200 °C for 26 h. After the heat preservation is completed, they are taken out and cooled with water.
[0050] A high-strength rare-earth magnesium alloy is prepared by the above preparation process. The atomic percentages of each element in its alloy composition are: nickel (Ni): 0.75%, gadolinium (Gd): 1.0%, samarium (Sm): 0.2 - 0.8%, and the rest are magnesium and other inevitable impurities.
[0051] The principle of the ratio design of Ni and Gd elements in this application is: when the atomic percentages of Ni element and Gd element are 3:4, the number of LPSO phases in the alloy is the largest and the distribution is the most dispersed. The principle of adding Sm element in this application is: adding different rare-earth elements simultaneously in the magnesium alloy will reduce the solid solubility of the rare-earth elements, thus increasing the number of precipitated LPSO phases. At the same time, there is a phenomenon that rare-earth elements can replace each other in the LPSO phase, which can further promote the precipitation of the LPSO phase. The atomic radius of Sm element is close to that of Gd element, and Sm element is the element with the largest solid solubility in the light rare-earth elements in the magnesium alloy (the solid solubility is about 5.8 wt.%). Therefore, Sm element can effectively replace Gd element in the LPSO phase and promote the formation of more LPSO phases.
[0052] Example 1:
[0053] The technical solution of this example is as follows:
[0054] (1) In terms of atomic percentage, the element composition of the high-strength rare-earth magnesium alloy in this example includes: Ni: 0.75%, Gd: 1.0%, Sm: 0.2%, and the balance is Mg and other inevitable impurities.
[0055] (2) The preparation method of the high-strength rare-earth magnesium alloy in this example includes the following processes:
[0056] 1) Melting:
[0057] ① Alloy raw material preparation: The total weight of each furnace of batching is 1.5 Kg. When batching, the burn-off ratio is adjusted according to the types and content ranges of alloy elements. The raw materials: pure magnesium (99.99 wt.%), Mg-25Ni (wt.%) master alloy, Mg-30Gd (wt.%) master alloy, Mg-30Sm (wt.%) master alloy are machined into suitable-sized blocks, and the oxide films on their surfaces are polished off with coarse sandpaper. After the alloy is polished brightly, it is packed in a sealed bag and reserved for use;
[0058] ②Resistance furnace heating: Set the temperature control program of the resistance furnace. First, heat the resistance furnace to 600 °C. After the temperature in the furnace stabilizes, heat the resistance furnace to 750 °C. At the same time, dry and preheat the crucible coated with boron nitride release agent.
[0059] ③Adding master alloys: After the crucible is completely dried and preheated to over 300 °C, place pure magnesium in the crucible and then place the crucible in the resistance furnace. At the same time, introduce a protective atmosphere of SF6 + CO2 (volume ratio approximately 1:99). After the pure magnesium is completely melted, add Mg-25Ni (wt.%) master alloy, Mg-30Gd (wt.%) master alloy, and Mg-30Sm (wt.%) master alloy into the stainless steel crucible in sequence. After they are completely melted, adjust the furnace temperature to 730 °C and hold for 10 min.
[0060] ④Stirring and impurity removal: After powering off the resistance furnace, use an electric stirrer to stir from bottom to top for 5 min to make the alloy melt as homogeneous as possible in composition. After the resistance furnace returns to 720 °C and stands for 2 min, use a long-handled ladle to filter out impurities.
[0061] ⑤Cooling: After stirring and impurity removal, take out the crucible and slowly put it into cold water for water cooling. After cooling to room temperature, take out the alloy.
[0062] 2) Homogenization treatment: After turning the surface of the alloy ingot obtained by melting and casting smooth, wrap it with aluminum foil, and then completely bury it in a stainless steel crucible with graphite powder. Place the crucible in a heat treatment furnace. Set the temperature to rise from room temperature to 300 °C in 2 h, hold for 1 h, then rise to 530 °C in 2 h, hold for 12 h, and after the holding is completed, take it out and cool it with water.
[0063] 3) Hot extrusion: Process the alloy ingot after homogenization treatment into a cylindrical billet with a diameter of Φ80 mm. Preheat the alloy billet and the die at 420 °C for 2 h. After the preheating is completed, quickly load the die and the alloy billet into the extruder in sequence for forward extrusion. The cooling method after extrusion is water cooling. The extrusion parameters are as follows: extrusion temperature: 420 °C, extrusion speed: 1.5 - 2.5 m·min -1 , extrusion ratio: 10.24:1;
[0064] 4) Aging treatment: Cut the bar obtained after hot extrusion into cylindrical bars with a length of 70 mm. Wrap the cut bars with aluminum foil and bury them with graphite, place them in a crucible and hold at 200 °C for 26 h. After the holding is completed, take it out and cool it with water.
[0065] (3) The yield strength of this alloy is measured to be 356 MPa and the tensile strength is 385 MPa by a room temperature tensile mechanical property testing machine.
[0066] Example 2:
[0067] The technical solution of this embodiment is as follows:
[0068] (1) In atomic percentage, the elemental composition of the high-strength rare-earth magnesium alloy of this embodiment includes: Ni: 0.75%, Gd: 1.0%, Sm: 0.4%, and the balance is Mg.
[0069] (2) The preparation method of the high-strength rare-earth magnesium alloy of this embodiment includes the following processes:
[0070] 1) Melting:
[0071] ① Alloy raw material preparation: The total weight of each furnace charge is 1.5 Kg. During batching, the burn-off ratio is adjusted according to the types and content ranges of alloy elements. The raw materials: pure magnesium (99.99 wt.%), Mg-25Ni (wt.%) master alloy, Mg-30Gd (wt.%) master alloy, and Mg-30Sm (wt.%) master alloy are machined into suitable-sized blocks, and the oxide films on their surfaces are polished off with coarse sandpaper. After the alloy is polished to be shiny, it is packaged in a sealed bag for standby.
[0072] ② Resistance furnace temperature rise: Set the temperature control program of the resistance furnace. First, raise the temperature of the resistance furnace to 600 °C. After the temperature in the furnace is stable, raise the temperature of the resistance furnace to 750 °C. At the same time, dry and preheat the crucible coated with boron nitride release agent.
[0073] ③ Adding master alloys: After the crucible is completely dried and preheated to above 300 °C, place the pure magnesium in the crucible and then place the crucible in the resistance furnace. At the same time, introduce a protective atmosphere of SF6 + CO2 (volume ratio about 1:99). After the pure magnesium is completely melted, add the three master alloys of Mg-25Ni (wt.%) master alloy, Mg-30Gd (wt.%) master alloy, and Mg-30Sm (wt.%) into the stainless-steel crucible in sequence. After they are completely melted, adjust the furnace temperature to 730 °C and hold for 10 min.
[0074] ④ Stirring and impurity removal: After the resistance furnace is powered off, use an electric stirrer to stir from bottom to top for 5 min to make the alloy melt as uniform in composition as possible. After the resistance furnace returns to 720 °C and stands for 2 min, use a long-handled ladle to filter out impurities.
[0075] ⑤ Cooling: After stirring and impurity removal, take out the crucible and slowly put it into cold water for water cooling. After cooling to room temperature, take out the alloy.
[0076] 2) Homogenization treatment: After turning the surface of the alloy ingot obtained by melting smooth, wrap it with aluminum foil, and then bury it completely with graphite powder in a stainless-steel crucible. Place the crucible in a heat treatment furnace. Set the temperature to rise from room temperature to 300 °C in 2 h, hold for 1 h, then rise to 530 °C in 2 h, hold for 12 h, and after the holding is completed, take it out and cool it in water.
[0077] (3) Hot extrusion: The homogenized alloy ingot is processed into a cylindrical blank with a diameter of Φ80mm. The alloy blank and the die are preheated at 420°C for 2h. After the preheating is completed, the die and the alloy blank are quickly loaded into the extruder in sequence for forward extrusion. The cooling method after extrusion is water cooling. The extrusion parameters are as follows: extrusion temperature: 420°C, extrusion speed: 1.5 - 2.5m·min -1 , extrusion ratio: 10.24:1;
[0078] (4) Aging treatment: The bars obtained after hot extrusion are cut into cylindrical bars with a length of 70mm. The cut bars are wrapped with aluminum foil and buried with graphite, and then placed in a crucible and kept at 200°C for 26h. After the heat preservation is completed, they are taken out and cooled with water.
[0079] (3) The yield strength of this alloy is measured to be 358MPa and the tensile strength is 390MPa by a room temperature tensile mechanical property testing machine.
[0080] Example 3:
[0081] The technical solution of this example is as follows:
[0082] (1) In atomic percentage, the elemental composition of the high-strength rare-earth magnesium alloy in this example includes: Ni: 0.75%, Gd: 1.0%, Sm: 0.4%, and the balance is Mg.
[0083] (2) The preparation method of the high-strength rare-earth magnesium alloy in this example includes the following processes:
[0084] 1) Melting:
[0085] ① Preparation of alloy raw materials: The total weight of each furnace charge is 1.5 Kg. During batching, the burning loss ratio is adjusted according to the types and content ranges of alloy elements. The raw materials: pure magnesium (99.99wt.%), Mg-25Ni (wt.%) master alloy, Mg-30Gd (wt.%) master alloy, and Mg-30Sm (wt.%) master alloy are machined into suitable-sized blocks, and the oxide films on their surfaces are polished off with coarse sandpaper. After the alloy is polished to be shiny, it is packaged in a sealed bag for standby.
[0086] ② Heating up the resistance furnace: Set the temperature control program of the resistance furnace. First, heat up the resistance furnace to 600°C. After the temperature in the furnace is stable, heat up the resistance furnace to 750°C, and at the same time, dry and preheat the crucible coated with boron nitride release agent.
[0087] ③Add master alloys: After the crucible is completely dried and preheated to above 300 °C, place pure magnesium in the crucible, then place the crucible in a resistance furnace, and simultaneously introduce a protective atmosphere of SF6 + CO2 (volume ratio is approximately 1:99). After the pure magnesium is completely melted, add Mg-25Ni (wt.%) master alloy, Mg-30Gd (wt.%) master alloy, and Mg-30Sm (wt.%) master alloy into the stainless-steel crucible in sequence. After they are completely melted, adjust the furnace temperature to 730 °C and hold for 10 min.
[0088] ④Stirring and impurity removal: After cutting off the power of the resistance furnace, use an electric stirrer to stir from bottom to top for 5 min to make the alloy melt as uniform in composition as possible. After the resistance furnace returns to 720 °C and stands for 2 min, use a long-handled ladle to filter out impurities.
[0089] ⑤Cooling: After stirring and impurity removal, take out the crucible and slowly put it into cold water for water cooling. After cooling to room temperature, take out the alloy.
[0090] 2) Homogenization treatment: After turning the surface of the alloy ingot obtained by melting and casting smooth, wrap it with aluminum foil, and then bury it completely with graphite powder in a stainless-steel crucible. Place the crucible in a heat treatment furnace, set the temperature to rise from room temperature to 300 °C in 2 h, hold for 1 h, then rise the temperature to 530 °C in 2 h, hold for 12 h, and take it out for water cooling after the holding is completed.
[0091] 3) Hot extrusion: Process the alloy ingot after homogenization treatment into a cylindrical blank with a diameter of Φ80 mm. Preheat the alloy blank and the die at 420 °C for 2 h. After the preheating is completed, quickly load the die and the alloy blank into the extruder in sequence for forward extrusion. The cooling method after extrusion is water cooling. The extrusion parameters are as follows: extrusion temperature: 420 °C, extrusion speed: 1.5 - 2.5 m·min -1 ,extrusion ratio: 10.24:1;
[0092] 4) Aging treatment: Cut the bar obtained after hot extrusion into cylindrical bars with a length of 70 mm. Wrap the cut bars with aluminum foil and bury them with graphite, place them in a crucible and hold at 200 °C for 26 h, and take them out for water cooling after the holding is completed.
[0093] (3) The yield strength of this alloy is measured to be 355 MPa and the tensile strength is 396 MPa by a room-temperature tensile mechanical property testing machine.
[0094] Example 4:
[0095] The technical solution of this example is as follows:
[0096] (1) In terms of atomic percentage, the elemental composition of the high-strength rare-earth magnesium alloy in this example includes: Ni: 0.75%, Gd: 1.0%, Sm: 0.8%, and the balance is Mg.
[0097] (2) The preparation method of the high-strength rare-earth magnesium alloy in this embodiment includes the following processes:
[0098] 1) Melting:
[0099] ① Alloy raw material preparation: The total weight of each furnace charge is 1.5 Kg. During batching, the burning loss ratio is adjusted according to the types and content ranges of alloying elements. The raw materials: pure magnesium (99.99 wt.%), Mg-25Ni (wt.%) master alloy, Mg-30Gd (wt.%) master alloy, and Mg-30Sm (wt.%) master alloy are machined into appropriately sized blocks, and the oxide films on their surfaces are polished off with coarse sandpaper. After the alloy is polished to a bright finish, it is packaged in a sealed bag for standby.
[0100] ② Resistance furnace heating: Set the temperature control program of the resistance furnace. First, heat the resistance furnace to 600 °C. After the temperature in the furnace stabilizes, heat the resistance furnace to 750 °C. At the same time, dry and preheat the crucible coated with boron nitride release agent.
[0101] ③ Adding master alloys: After the crucible is completely dried and preheated to above 300 °C, place pure magnesium in the crucible and then place the crucible in the resistance furnace. At the same time, introduce a protective atmosphere of SF6 + CO2 (volume ratio approximately 1:99). After the pure magnesium is completely melted, add the three master alloys of Mg-25Ni (wt.%), Mg-30Gd (wt.%), and Mg-30Sm (wt.%) into the stainless-steel crucible in sequence. After they are completely melted, adjust the furnace temperature to 730 °C and hold for 10 min.
[0102] ④ Stirring and impurity removal: After the resistance furnace is powered off, use an electric stirrer to stir from bottom to top for 5 min to make the alloy melt as uniform in composition as possible. After the resistance furnace returns to 720 °C and stands for 2 min, use a long-handled ladle to filter out impurities.
[0103] ⑤ Cooling: After stirring and impurity removal, take out the crucible and slowly place it in cold water for water cooling. After cooling to room temperature, take out the alloy.
[0104] 2) Homogenization treatment: After turning the surface of the alloy ingot obtained by melting smooth, wrap it with aluminum foil, and then bury it completely with graphite powder in a stainless-steel crucible. Place the crucible in a heat treatment furnace, set the temperature to rise from room temperature to 300 °C in 2 h, hold for 1 h, then rise to 530 °C in 2 h, hold for 12 h, and after the holding ends, take it out for water cooling.
[0105] (3) Hot extrusion: The homogenized alloy ingot is processed into a cylindrical blank with a diameter of Φ80mm. The alloy blank and the die are preheated at 420°C for 2h. After the preheating is completed, the die and the alloy blank are quickly loaded into the extruder in sequence for forward extrusion. The cooling method after extrusion is water cooling. The extrusion parameters are as follows: extrusion temperature: 420°C, extrusion speed: 1.5 - 2.5m·min -1 , extrusion ratio: 10.24:1.
[0106] (4) Aging treatment: The bars obtained after hot extrusion are cut into cylindrical bars with a length of 70mm. The cut bars are wrapped with aluminum foil and buried with graphite, and then placed in a crucible and kept at 200°C for 26h. After the heat preservation is completed, they are taken out and cooled with water.
[0107] (3) The yield strength of this alloy is measured to be 393MPa and the tensile strength is 417MPa by a room temperature tensile mechanical property testing machine.
[0108] Comparative Example 1:
[0109] The technical solution of this example is as follows:
[0110] (1) In atomic percentage, the elemental composition of the high-strength rare-earth magnesium alloy in this example includes: Ni: 0.75%, Gd: 1.0%, and the balance is Mg.
[0111] (2) The preparation method of the high-strength rare-earth magnesium alloy in this example includes the following processes:
[0112] 1) Melting:
[0113] ① Preparation of alloy raw materials: The total weight of each furnace charge is 1.5 Kg. When charging, the burn-off ratio is adjusted according to the types and content ranges of alloy elements. The raw materials: pure magnesium (99.99wt.%), Mg-25Ni (wt.%) master alloy, Mg-30Gd (wt.%) master alloy, Mg-30Sm (wt.%) master alloy are machined into suitable-sized blocks, and the oxide films on their surfaces are polished off with coarse sandpaper. After the alloy is polished brightly, it is packed in a sealed bag for standby.
[0114] ② Heating up the resistance furnace: Set the temperature control program of the resistance furnace. First, heat up the resistance furnace to 600°C. After the temperature in the furnace is stable, heat up the resistance furnace to 750°C, and at the same time, dry and preheat the crucible coated with boron nitride release agent.
[0115] ③Add master alloys: After the crucible is completely dried and preheated to over 300 °C, place pure magnesium in the crucible and then put the crucible into a resistance furnace. At the same time, introduce a protective atmosphere of SF6+CO2 (volume ratio approximately 1:99). After the pure magnesium is completely melted, add three master alloys, namely Mg-25Ni (wt.%), Mg-30Gd (wt.%), and Mg-30Sm (wt.%) into the stainless-steel crucible in sequence. After they are completely melted, adjust the furnace temperature to 730 °C and hold for 10 min.
[0116] ④Stirring and impurity removal: After powering off the resistance furnace, use an electric stirrer to stir from bottom to top for 5 min to make the alloy melt as uniform in composition as possible. After the resistance furnace returns to 720 °C and stands for 2 min, use a long-handled ladle to filter out impurities.
[0117] ⑤Cooling: After stirring and impurity removal, take out the crucible and slowly put it into cold water for water cooling. After cooling to room temperature, take out the alloy.
[0118] 2) Homogenization treatment: After turning the surface of the alloy ingot obtained by melting and casting smooth, wrap it with aluminum foil, and then bury it completely with graphite powder in a stainless-steel crucible. Place the crucible in a heat treatment furnace, set the temperature to rise from room temperature to 300 °C in 2 h, hold for 1 h, then rise the temperature to 530 °C in 2 h, hold for 12 h, and after the holding is completed, take it out for water cooling.
[0119] 3) Hot extrusion: Process the alloy ingot after homogenization treatment into a cylindrical blank with a diameter of Φ80 mm. Preheat the alloy blank and the die at 420 °C for 2 h. After the preheating is completed, quickly load the die and the alloy blank into the extruder in sequence for forward extrusion. The cooling method after extrusion is water cooling. The extrusion parameters are as follows: extrusion temperature: 420 °C, extrusion speed: 1.5 - 2.5 m·min -1 and extrusion ratio: 10.24:1;
[0120] 4) Aging treatment: Cut the bar obtained after hot extrusion into cylindrical bars with a length of 70 mm. Wrap the cut bars with aluminum foil and bury them with graphite, place them in a crucible and hold at 200 °C for 26 h. After the holding is completed, take it out for water cooling.
[0121] (3) The yield strength of this alloy is measured to be 348 MPa and the tensile strength is 367 MPa by a room-temperature tensile mechanical property testing machine.
[0122] Table 1 Elemental composition (at%, atomic percentage) of the magnesium alloys in Examples 1 - 4 and Comparative Example 1
[0123] Ni Gd Sm Mg Comparative Example 1 0.75 1.0 - balance Example 1 0.75 1.0 0.2 balance Example 2 0.75 1.0 0.4 balance Example 3 0.75 1.0 0.6 balance Example 4 0.75 1.0 0.8 balance
[0124] Table 2 Tensile mechanical properties of the magnesium alloys in Examples 1 - 4 and Comparative Example 1
[0125] Yield strength (MPa) Tensile strength (MPa) Comparative Example 1 348 367 Example 1 356 385 Example 2 358 390 Example 3 355 396 Example 4 393 417
[0126] Please refer to Figures 2 to 4 , in the present invention, by adding Sm element into the magnesium alloy and combining with hot extrusion and heat treatment processes, the LPSO phase in the magnesium alloy is effectively regulated. The number of LPSO phases increases, the size is finer and the distribution is more dispersed, and the strength of the magnesium alloy is significantly improved, obtaining a high-strength magnesium alloy with a yield strength of 356 - 393 MPa and a tensile strength of 385 - 417 MPa.
[0127] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit them. Although the present invention has been described in detail with reference to the preferred embodiments, those of ordinary skill in the art should understand that the technical solutions of the present invention can be modified or equivalently replaced without departing from the purpose and scope of the present technical solution, and they should all be covered within the scope of the claims of the present invention.
Claims
1. A preparation process of a high-strength rare earth magnesium alloy, characterized in that, It includes the following steps: (1) Melting: Melting pure magnesium, Mg-25Ni master alloy, Mg-30Gd master alloy and Mg-30Sm master alloy into alloy ingots; (2) Homogenization treatment: After turning the surface of the alloy ingot smooth, wrapping it with aluminum foil, then burying it in a medium crucible with graphite powder, placing the crucible in a heat treatment furnace, heating up to 300°C and holding for 1 hour, then heating up to 530°C and holding for 12 hours, and water cooling after the holding is completed; (3) Hot extrusion: The homogenized alloy ingot is processed into a cylindrical blank, and both the blank and the die are preheated, then loaded into an extrusion press for forward extrusion. The extrusion parameters are: extrusion temperature 420°C, extrusion speed 1.5 - 2.5 m·min -1 , extrusion ratio 10.24:1, followed by water cooling after extrusion; (4) Aging treatment: Cutting the hot-extruded bar into cylindrical bars, then wrapping them with aluminum foil, burying them in a medium crucible with graphite powder, and holding at 200°C for 26 hours, and water cooling after the holding is completed.
2. The preparation process according to claim 1, wherein Step (1) includes the following steps: a) Alloy raw material preparation: Machining pure magnesium, Mg-25Ni master alloy, Mg-30Gd master alloy and Mg-30Sm master alloy into blocks and grinding off the oxide film on their surfaces; b) Resistance furnace heating: First heating the resistance furnace to 600°C, and then heating to 750°C after the temperature stabilizes, while drying and preheating the crucible; c) Adding master alloy: After the crucible is preheated to above 300°C, placing pure magnesium in the crucible, placing the crucible in the resistance furnace, introducing a protective atmosphere of SF6+CO2, after the pure magnesium melts, successively adding Mg-25Ni, Mg-30Gd and Mg-30Sm master alloys, and adjusting the furnace temperature to 730°C after complete melting and holding for 10 minutes; d) Stirring and impurity removal: Stirring for 5 minutes after power-off, then warming the resistance furnace back to 720°C, standing for 2 minutes and filtering off impurities; e) Cooling: Taking out the crucible and cooling it in cold water to room temperature, and taking out the alloy ingot.
3. The preparation process according to claim 2, wherein, In step (1) a), the purity of the pure magnesium is 99.99wt.%.
4. The preparation process according to claim 2, characterized in that, In step (1) c), the volume ratio of the protective atmosphere SF6+CO2 is 1:
99.
5. The preparation process according to claim 2, characterized in that, In step (1) d), using a long-handled ladle to filter off impurities.
6. The preparation process according to claim 1, characterized in that, In step (2), the time for heating up to 300°C is 2 hours, and the time for heating up to 530°C is 2 hours.
7. The preparation process according to claim 1, wherein In step (3), the preheating temperature of the die and the alloy blank is 420°C, and the preheating time is 2 hours.
8. The preparation process according to claim 1, characterized in that, In step (3), processing the homogenized alloy ingot into a cylindrical blank with a diameter of Φ80mm; In step (4), cutting the hot-extruded bar into cylindrical bars with a length of 70mm.
9. The preparation process according to claim 1, characterized in that, The atomic percentages of each element in the alloy composition of the alloy ingot are: Ni: 0.75%, Gd: 1.0%, Sm: 0.2-0.8%, and the rest is Mg.
10. A high-strength rare earth magnesium alloy, characterized in that, Prepared by the preparation process described in any one of claims 1-8, and the atomic percentages of each element in its alloy composition are: Ni: 0.75%, Gd: 1.0%, Sm: 0.2-0.8%, and the rest is Mg.
Citation Information
Patent Citations
Nickel-containing heat resisting magnesium-rare earth alloy and preparation method thereof
CN101392345A
Single-phase solid solution cast or wrought magnesium alloys
US20120195787A1